Integrative single-cell and spatial transcriptomics analysis reveals FLAD1 as a regulator of the immune microenvironment in hepatocellular carcinoma - Zhu, Peng; Mou, Lisha; Lu, Ying; Pu, Zuhui; Guo, Changchun (Frontiers in Immunology, 2025)
Hepatocellular carcinoma (HCC) remains one of the leading causes of cancer-related mortality worldwide, characterized by increasing incidence rates and challenging prognoses. This study integrates single-cell RNA sequencing (scRNA-seq) and spatial transcriptomics to unravel the complex molecular and structural landscape of HCC, focusing on the identification of mitochondrial-related genes (MitRGs) and their pivotal role in disease progression. Utilizing scRNA-seq and bulk RNA-seq data, we performed a comprehensive differential expression analysis to highlight MitRGs. A modeling approach using 92 combinations of nine machine learning algorithms was applied, producing a predictive model with good performance. Among the genes analyzed, FLAD1 emerged as significantly upregulated in HCC tissues, correlating with advanced disease stages and poorer patient outcomes, and exhibited exceptional diagnostic accuracy with an AUC of 0.962. Functional enrichment analyses revealed that high FLAD1 expression is involved in crucial biological processes like copper ion detoxification and heme complex assembly. Interaction networks further elucidated the connection between FLAD1 and critical HCC pathways, with its expression levels negatively correlated with key immune effector cells such as CD8+ T cells and DCs. Spatial transcriptomics analysis provided a structural basis for this immune exclusion, demonstrating that an intact tumor capsule can function as a physical barrier that fosters an immune-exempt microenvironment. This analysis also validated FLAD1 upregulation within the spatial context of the tumor. Additionally, DNA methylation analysis indicated a hypomethylation pattern in the FLAD1 promoter region, likely contributing to its overexpression in HCC. Validation of FLAD1 protein levels in an in-house cohort via Western blotting further confirmed these findings. Collectively, our integrative study highlights the utility of MitRGs as potential biomarkers and positions FLAD1 as a dual prognostic and therapeutic target linked to the structural and immune landscape of HCC.